A novel approach towards the calculation of dose rate constants for ambient dose equivalent H∗(10) by including low energy x-rays. (December 2021) - Stettner, Christoph; Baumgartner, Nadine; Hranitzky, Christian; Poljanc, Karin; Stadtmann, Hannes; Streli, Christina
Abstract: The nuclide-specific dose rate constant, formerly called gamma ray constant, is one of the most important quantities in practical radiation protection dosimetry. For radiation sources with known radionuclide composition and activity, the expected dose rates at various distances can easily be calculated with reasonable approximations. In addition, they serve as a planning basis for the design of shielding of radiation application rooms and facilities. In this study, dose rate constants were calculated using the most recent conversion coefficients and the most suitable spectral data for more than 400 radionuclides using different calculation approaches. In addition this paper provides a critical review of currently published dose rate constants for the ambient dose equivalent H ∗ ( 10 ) . Graphical abstract: Highlights: In a novel approach, x-rays are considered for dose rate constants and applied for the calculation of 400 radionuclides. Comparison of different approaches for calculating dose rate constants. Comparison of different conversion coefficients published bei IRCU 57, ICRP 74 and ISO 4037-3. Evaluation of published dose rate constants for radionuclides in different energy ranges. Investigation of possible causes for the discrepancies between the published data.